Investigation of the indoor environment of a passive house office building under cold climate in China. Issue 3 (March 2023) - HE, Yueer; HAN, Fei; ZHAO, Lingmin; LI, Shuanggen
This study analyzed the applicability of the Passive House standard to office buildings in northern China from an indoor environment perspective. The case building has been auto-monitored continuously since 2017 and a survey for instantaneous and retrospective appraisal of indoor environmental conditions was administered in 2021 during the summer, winter and months in between, referred to as 'transition months'. The results show that indoor environment quality was good, with high satisfaction levels and ultra-low energy consumption; overheating and the need for window opening were observed. The prevalence of sick building syndrome was reduced compared to conventional buildings. This work further determined how comfort parameters such as perceived thermal comfort, indoor air quality and acoustics could affect end-users' appraisal. Findings show that indoor thermal comfort design parameters, particularly in summer, are critical factors affecting users' satisfaction in Passive Houses. We further examined the feasibility of the PMV-PPD index for predicting occupants' perceived comfort and suggested deriving the preferred thermal comfort design parameters for the Chinese market, using long-term data and measurements. These findings provide insights into the localization of Passive Houses in China, thereby improving the acceptance of Passive Houses in what is expected to be a fast growing market.